Order Evolution in Iron-Based Alloys Viewed through Amplitude Dependent Damping Studies - Lambri, Osvaldo Agustin F. (2015)
Amplitude dependent damping and neutron thermo-diffraction studies were performed in Fe-Al-Si, Fe-Al-Cr and Fe-Si alloys. Results show that the behaviour of the strength of the amplitude dependent damping as a function of temperature is a suitable tool for determining the order changes as a function of temperature. A decrease in the order degree leads to an increase in the strength of the amplitude dependent damping, due to the dislocation mobility increases.